2024
DOI: 10.1002/anie.202314728
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Echinocandin Antifungal Drugs To Circumvent Glucan Synthase Point‐Mutation‐Mediated Resistance

Moriah Jospe‐Kaufman,
Efrat Ben‐Zeev,
Austin Mottola
et al.

Abstract: Echinocandins are a class of antifungal drugs that inhibit the activity of the β‐(1,3)‐glucan synthase complex, which synthesizes fungal cell wall β‐(1,3)‐glucan. Echinocandin resistance is linked to mutations in the FKS gene, which encodes the catalytic subunit of the glucan synthase complex. We present a molecular docking‐based model that provides insights into how echinocandins interact with the target Fks protein: echinocandins form a ternary complex with both Fks and membrane lipids. We used reductive deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is also possible that echinocandins directly interact with lipid molecules within the binding pocket, and thereby modify GS enzymatic activity. Recent docking simulations have suggested that the lipophilic tail of echinocandins may form a ternary complex with these bound lipids 39 . Further studies will be necessary to determine the molecular details of these interactions and to understand how specific lipid molecules, such as sphingolipids and ergosterols, influence echinocandin activity and the development of antifungal resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that echinocandins directly interact with lipid molecules within the binding pocket, and thereby modify GS enzymatic activity. Recent docking simulations have suggested that the lipophilic tail of echinocandins may form a ternary complex with these bound lipids 39 . Further studies will be necessary to determine the molecular details of these interactions and to understand how specific lipid molecules, such as sphingolipids and ergosterols, influence echinocandin activity and the development of antifungal resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the antifungal drugs of natural origin currently in clinical use belong to either the polyene class, such as amphotericin B, nystatin, and natamycin, or to the echinocandin class, which includes caspofungin, anidulafungin, and micafungin (Baginski & Czub, 2009 ; Houšť et al, 2020 ). Echinocandins, which are not fully natural, are a highly selective class of semisynthetic lipopeptides that inhibit the synthesis of 1,3‐β‐glucans, important constituents of the fungal cell wall (Jospe‐Kaufman et al, 2024 ). Due to their mechanism of action, which is analogous to β‐lactam antibiotics in bacteria (i.e., inhibition of cell wall synthesis), this class of compounds is often termed the “penicillin of antifungals.” Several new compounds with antifungal activity, both natural and synthetic (e.g., nikkomycin Z, griseofulvin, olorofim, rezafungin, fosmanogepix, ibrexafungerp, opelconazole, and encochleated), have been developed through various scientific research programs and are in the process of being approved by major regulatory agencies, such as the FDA (Boutin & Luong, 2024 ).…”
Section: Therapeutic Drugs Of Microbial Originmentioning
confidence: 99%